Prevalence of Chlamydia trachomatis in young men in north west London. Issue 4 (1st August 2000) - Pierpoint, Tracey; Thomas, Brenda; Judd, Ali; Brugha, Ruairí; Taylor-Robinson, David; Renton, Adrian
Abstract : Background: Chlamydia trachomatis is the most common, treatable, bacterial sexually transmitted infection in England and Wales. Among men, chlamydial infection is an important cause of non-gonococcal urethritis, epididymitis, and proctitis. The case for wider screening among women has been accepted by an expert advisory group. In the absence of estimates of the prevalence of infection in men, its potential impact at the population level is difficult to assess. Objective: To estimate the prevalence of Chlamydia trachomatis in young men in clinic and community based samples in north west London. Method: Cross sectional survey in healthcare centres and general practices in north west London. 1002 males aged 18–35 years, living in north west London, were recruited by staff in occupational health departments, general practices, student health services, and a "well man" clinic and by postal recruitment in four GP practices. The men were tested for C trachomatis using the ligase chain reaction assay on urine samples. The main outcome measure was prevalence of C trachomatis infection in men aged 18–35 years. Results: The overall response rate was 51%. Prevalence of confirmed infection was 1.9% (95% CI: 1.14% to 2.96%) in all men. Best estimated minimum prevalence of infection was 1% (95% CI: 0.58% to 1.50%). Estimated prevalence was highest among men aged over 30 years. Conclusions: The estimated prevalence among men is commensurate with that described for female populations in London. The results suggest that recruitment of men to screening programmes would be difficult. However, a higher proportion of chlamydial infection may be detected in men than in women by existing approaches to control through genitourinary medicine clinic based case finding and contact tracing. Screening of young women and the contact tracing of the male partners of positive females may be an efficient approach to improving chlamydia control.